Is memantine a potential therapeutic for Rett syndrome? - Bello, Olivia; Blair, Kelsey; Chapleau, Christopher; Larimore, Jennifer (Frontiers in Neuroscience, 2013)
Memantine is a low-affinity voltage-dependent non-competitive N-methyl-D-aspartate (NMDA) receptor antagonist. It is classified as a neuroprotective aminoadamantane. It does not cure or reverse Alzheimer’s but it does effectively treat symptoms, slows the progression of the disease and allows many patients to perform daily cognitive activities with clear thoughts. Based on it’s success in patients with Alzheimer’s, memantine has been tested in other neurological disorders with impaired learning and memory. In this review, we will discuss the success and failures of memantine in Downs Syndrome and Fragile X research and from those results, assess the potential benefit of memantine in Rett Syndrome.